The Relationship Between Self-Confidence and Anxiety to OSCE Results in First Year Students of Faculty Medicine, Universitas Muhammadiyah Surabaya - Farhan, Hafidz Muhammad; Levani, Yelvi; Prasetya, Era Chess (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2025)
OSCE (Objective Structured Clinical Examination) is a clinical skills assessment method to improve student clinical skills and prepare competent graduates. Factors that influence OSCE include self-confidence and anxiety. So that good management of self-confidence and anxiety will be an indicator of successful OSCE results. This study aims to determine whether there is a relationship between self-confidence and anxiety to the performance of OSCE results in first year students of Faculty Medicine, Muhammadiyah University of Surabaya. This study used a cross-sectional design with total sampling. The sample was first year students (106) of the Faculty of Medicine, Universitas Muhammadiyah Surabaya, Batch 2023. The instruments used were the RSES questionnaire to assess the level of self-confidence and the HARS questionnaire to determine the level of anxiety. Data analysis was performed using the Spearman test. There is no relationship between self-confidence and anxiety on the performance of OSCE results in first year students of the Faculty of Medicine, Muhammadiyah University of Surabaya.